Integrated analysis of chromatin and transcriptomic profiling of the striatum after cerebral hypoperfusion in mice - Shijia Le; Fengyiyang Xu; Zhi Luo; Weihao Shi; Shuangshuang Lu; Zengyu Zhang; Zimin Guo; Wenshi Xu; Mingqi Yang; Tianyi Li; Xu Li; Kun Liang; et al. (BMC Genomics)
Abstract Background Vascular cognitive impairment (VCI) is a significant contributor to dementia, yet the precise mechanisms underlying the cognitive decline associated with chronic cerebral hypoperfusion (CCH) remain unclear. This study investigated the molecular and epigenetic changes in the striatum, a brain region critical for motor function and cognition, following chronic hypoperfusion using a bilateral common carotid artery stenosis (BCAS) model in mice. Methods RNA-seq was utilized to identify differentially expressed genes (DEGs) associated with hypoperfusion. In parallel, ATAC-seq was used to assess changes in chromatin accessibility within the striatum, providing insight into the epigenome and potential regulatory mechanisms. The integration of these datasets allowed us to correlate chromatin accessibility with transcriptional activity and to identify key transcription factors driving the observed gene expression changes. Results Analysis of striatum-specific transcriptome revealed significant upregulation of immune response genes, particularly type II interferon signaling, and downregulation of neural activation pathways. Analysis of striatum-specific epigenome showed increased chromatin accessibility at promoters of immune-related genes. Integrated analysis highlighted PU.1 as a key transcription factor in upregulated pathways, while neural pathways lacked epigenetic regulation, revealing distinct molecular responses in the striatum following chronic hypoperfusion. Conclusions Our findings indicate that upregulated pathways in the striatum following BCAS-induced CCH are driven by epigenetic changes, while downregulated pathways occur independently of these modifications. Additionally, PU.1 plays a critical role in mediating immune responses, offering a potential target for therapeutic intervention.